Incorporation of catechyl monomers into lignins: lignification from the non-phenolic end via Diels–Alder cycloaddition?. Issue 22 (26th October 2021) - Ando, Daisuke; Lu, Fachuang; Kim, Hoon; Eugene, Alexis; Tobimatsu, Yuki; Vanholme, Ruben; Elder, Thomas J.; Boerjan, Wout; Ralph, John
Abstract : Catechyl monomers 1-electron-oxidize and undergo radical coupling to produce benzodioxane units in lignin. Derived o -quinones undergo Diels–Alder reactions giving oxatricyclo and new benzodioxane products, but does this occur in lignification?. Abstract : Canonical lignification occurs via the coupling of phenolic radicals, in which chain extension can occur only from phenolic ends of growing polymer chains. Radical coupling of catechyl monomers, including caffeyl and 5-hydroxyconiferyl alcohols, gives rise to benzodioxane units in the polymer. Anticipating that a catechol could oxidize to its o -benzoquinone analog under the dehydrogenative (oxidative) conditions of lignification, we examined the possibility that an o -benzoquinone, as the diene component, could also incorporate into lignin via another mechanism, the Diels–Alder cycloaddition reaction. The o -benzoquinone derived from methyl 5-hydroxyvanillate and 4- O -methylconiferyl alcohol served as models for the diene and dienophile, respectively, and produced Diels–Alder products in vitro . Two types of Diels–Alder products were found: (i) when the 1, 2-diketone of the quinone acts as the diene in a hetero-Diels–Alder reaction, a benzodioxane structure was produced with a different regiochemistry than the benzodioxane isomer produced via radical coupling; (ii) when the quinone's diene participated in the Diels–Alder reaction, a distinctive oxatricyclo structure was produced. Both features may be used as markers for the occurrence of Diels–Alder reactions in lignification. Examination of natural lignins derived from catechyl monomers, however, did not reveal evidence for such products. The conclusion is that the only significant reactions in lignification are combinatorial radical coupling reactions of the single-electron-oxidized phenolics and that polymer chain extension therefore occurs only from the phenolic end-units even in the special case of plants that utilize catechyl monomers for lignification.